(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
Seven of the sites identified during the survey were selected for further evaluation as they were either of potentially early date (pre-19th century) or might conceal earlier features. Three of these sites were then subject to more substantial excavation on the basis of the evaluation results. The sites are described one by one and include shieling huts and circular stone features (sites 3-6), shieling huts and cultivation rigs (site 8), a rectangular turf structure (site 10), a township (site 15), a rectangular building (site 26) and a kerb cairn (site 41). Radiocarbon dates and lithics are also reported on.